The Role of Temperature in Shaping Mosquito-Borne Viruses Transmission - Bellone, Rachel; Failloux, Anna-Bella (Frontiers in Microbiology, 2020)
Mosquito-borne diseases are typically prevalent in the tropical belt of the world. However, these diseases are conquering temperate regions, raising the question of the role of temperature on their dynamics and expansion. Temperature is one of the most significant abiotsic factors affecting, in many ways, insect vectors and the pathogens they transmit. Here, we debate the truth of this claim by synthesizing current knowledge on the effects of temperature on arboviruses and their vectors, as well as the outcome of their interactions.